Mechanisms and Neuroprotective Activities of Stigmasterol Against Oxidative Stress-Induced Neuronal Cell Death via Sirtuin Family - Pratiwi, Reny; Nantasenamat, Chanin; Ruankham, Waralee; Suwanjang, Wilasinee; Prachayasittikul, Virapong; Prachayasittikul, Supaluk; Phopin, Kamonrat (Frontiers in Nutrition, 2021)
Background: Accumulating studies have confirmed that oxidative stress leads to the death of neuronal cells and associated with the progression of neurodegenerative diseases, including Alzheimer’s disease (AD). Despite the compelling evidence, there is a drawback on the use of antioxidant approach for AD treatment, partly due to the limited blood-brain barrier (BBB) permeability. Phytosterol is known to exhibit BBB penetration and exerts various bioactivities such as antioxidant, anticancer, as well as displays a potential treatment for dyslipidemia, cardiovascular disease, and dementia. Objective: In this study, the protective effects of stigmasterol, a phytosterol compound, on cells death induced by hydrogen peroxide (H2O2) were examined in vitro using human neuronal cells (SH-SY5Y cells). Methods: MTT assay, reactive oxygen species measurement, mitochondrial membrane potential assay, apoptotic cell measurement, and protein expression profiles were performed to determine neuroprotective properties of stigmasterol. Results: H2O2 exposure significantly increased the levels of reactive oxygen species (ROS) within the cells thereby inducing apoptosis. On the contrary, pretreatment with stigmasterol maintained ROS levels inside the cells and prevented oxidative stress-induced cell death. It was found that pre-incubation with stigmasterol also facilitated upregulation of forkhead box O (FoxO) 3a, catalase, and anti-apoptosis protein B-cell lymphoma 2 (Bcl-2) in the neurons. In addition, expression levels of sirtuin 1 (SIRT1) were also increased while acetylated lysine levels were decreased, indicating that SIRT1 activity was stimulated by stigmasterol, and the result was comparable with the known SIRT1 activator, resveratrol. Conclusion: Taken together, these results suggest that stigmasterol could be potentially useful to alleviate neurodegeneration induced by oxidative stress.